Insights and future directions for the application of perinatal derivatives in eye diseases: A critical review of preclinical and clinical studies - Norte-Muñoz, María; Botelho, Maria Filomena; Schoeberlein, Andreina; Chaves, João; Neto Murta, Joaquim; Ponsaerts, Peter; Agudo-Barriuso, Marta; Costa, Esmeralda (Frontiers in Bioengineering and Biotechnology, 2022)
Perinatal derivatives (PnD) are gaining interest as a source for cell-based therapies. Since the eye is easily accessible to local administration, eye diseases may be excellent candidates to evaluate novel therapeutic approaches. With this work, we performed a systematic review of published preclinical and clinical studies addressing PnD in the treatment of ocular diseases. We have set two specific objectives: (i) to investigate the current level of standardization in applied technical procedures in preclinical studies and (ii) to assess clinical efficacy in clinical trials. Hereto, we selected studies that applied amniotic membrane (hAM) and mesenchymal stromal cells derived from amniotic membrane (hAMSC), placenta (hPMSC), umbilical cord (hUC-MSC) and Wharton's Jelly (hUC-WJ-MSC), excluding those where cells were not transplanted individually, following a systematic PubMed search for preclinical studies and consultation of clinical studies on https://clinicaltrials.gov and https://www.clinicaltrialsregister.eu/. Our bibliographic search retrieved 26 pre-clinical studies and 27 clinical trials. There was a considerable overlap regarding targeted ocular structures. Another common feature is the marked tendency towards (i) locally administered treatments and (ii) the PnD type. In the cornea/ocular surface, hAM was preferred and usually applied directly covering the ocular surface. For neuroretinal disorders, intra-ocular injection of umbilical or placental-derived cells was preferred. In general, basic research reported favourable outcomes. However, due to lack of standardization between different studies, until now there is no clear consensus regarding the fate of administered PnD or their mode of action. This might be accountable for the low index of clinical translation. Regarding clinical trials, only a minority provided results and a considerable proportion is in “unknown status”. Nevertheless, from the limited clinical evidence available, hAM proved beneficial in the symptomatic relief of bullous keratopathy, treating dry eye disease and preventing glaucoma drainage device tube exposure. Regarding neuroretinal diseases, application of Wharton’s Jelly MSC seems to be to become a promising future approach. In conclusion, PnD-based therapies seem to be beneficial in the treatment of several ocular diseases. However, much is yet to be done both in the pre-clinical and in the clinical setting before they can be included in the daily ophthalmic practice.